Entrepreneurial Ethics, Buddhist Leadership Behavior, and Entrepreneurial Spirit Among Undergraduate Students in A Buddhist Business and Management Program - Febrianus, Febrianus; Nyanasuryanadi, Partono; Khiong, Khie (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study examines the influence of entrepreneurial ethics and Buddhist leadership behavior on entrepreneurial spirit among undergraduate students in a Buddhist Business and Management program. The study aims to explore how value-based education contributes to the development of entrepreneurial readiness beyond cognitive knowledge. A quantitative approach with a survey design was employed in this study. The population consisted of all undergraduate students in the Buddhist Business and Management Program at STIAB Smaratungga. Because the population was relatively small, a total sampling technique was applied, resulting in 31 students as the research sample. Primary data were collected through a structured questionnaire using a Likert scale and were analyzed using multiple linear regression with SPSS version 26. The results show that entrepreneurial ethics and Buddhist leadership behavior do not have significant effects when examined individually, but jointly have a significant effect on entrepreneurial spirit. This indicates that entrepreneurial development is not driven by isolated factors but emerges through the interaction of ethical values and leadership behavior within the educational environment. The study concludes that strengthening entrepreneurial spirit requires an integrative learning approach that connects ethical understanding, leadership values, and experiential practice. These findings provide important insights for developing value-based entrepreneurship education and improving educational strategies in cultivating responsible and resilient future entrepreneurs.